Power system analysis - Gross, Charles A. (Wiley, 1979)
Provides a basic comprehensive treatment of the major electrical engineering problems associated with the design and operation of electric power systems. The major components of the power system are modeled in terms of their sequence (symmetrical component) equivalent circuits. Reviews power flow, fault analysis, economic dispatch, and transient stability in power systems.